2015
DOI: 10.1007/s12035-015-9197-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bisphenol-A Mediated Inhibition of Hippocampal Neurogenesis Attenuated by Curcumin via Canonical Wnt Pathway

Abstract: Bisphenol A (BPA) is an environmental xenoestrogenic endocrine disruptor, utilized for production of consumer products, and exerts adverse effects on the developing nervous system. Recently, we found that BPA impairs the finely tuned dynamic processes of neurogenesis (generation of new neurons) in the hippocampus of the developing rat brain. Curcumin is a natural polyphenolic compound, which provides neuroprotection against various environmental neurotoxicants and in the cellular and animal models of neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 90 publications
(132 reference statements)
7
52
0
Order By: Relevance
“…previous studies demonstrated that BPA exposure inhibits NSC proliferation and differentiation and also causes neurodegeneration in the hippocampus (1)(2)(3). In the present study, we found increased mitochondrial fission, increased oxidative stress, and apoptosis.…”
Section: Bpa-mediated Increased Apoptosis and Inhibition Of Nsc Prolisupporting
confidence: 76%
See 4 more Smart Citations
“…previous studies demonstrated that BPA exposure inhibits NSC proliferation and differentiation and also causes neurodegeneration in the hippocampus (1)(2)(3). In the present study, we found increased mitochondrial fission, increased oxidative stress, and apoptosis.…”
Section: Bpa-mediated Increased Apoptosis and Inhibition Of Nsc Prolisupporting
confidence: 76%
“…Hippocampal NSC Culture-Hippocampus-derived NSC culture was carried out following our previous studies (2,3,62). Briefly, pregnant Wistar rats were deeply anesthetized with a mixture of ketamine and xylazine (3:1 ratio) and dissected cautiously to remove the embryos at embryonic day 12.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations